Activities of the wintering party of the 17th Japanese Antarctic Research Expedition in 1976-1977 - Takeo Yoshino (National Institute of Polar Research, 1981)
Twenty-nine members of the wintering party occupied Syowa Station from February 1,1976 to January 31,1977,carrying out the preparation and observations in accordance with the program of the first year of research projects of the International Magnetospheric Study (IMS). At Syowa Station, in addition to the observation of aurora, geomagnetism, ionosphere, meteorology, seismology, marine morphology, ocean tide, and medical science, the major research program covers the preparation of many observation apparatuses for upper atmosphere physics, as well as the construction of satellite tracking and telemetry facilities, the reception of telemetry signals from scientific satellites, and the launching of seven (five in winter) sounding rockets and one big balloon to carry out the IMS project. Mizuho Station was improved for upper atmospheric observations in connection with the IMS program including the construction of one observation hut and the setting up of a 16kVA generator in May 1976,and occupied by four members in rotation so as to carry out observations of upper atmosphere physics, glaciology, and meteorology from May 14,1976 to January 26,1977.